Analisis Pengaruh Model Pembelajaran Course Review Horay (CRH) Terhadap Hasil Belajar Siswa Sekolah Dasar - Mirtha Absari; Deni Adi Putra; Fitroh Setyo Putro Probowo (Universitas PGRI Adi Buana Surabaya, 2021)
This study aims to analyze the effect of the Course Review Horay (CRH) learning model on learning outcomes of elementary school students. This is because there are still many teachers who use conventional learning methods, causing students to feel bored and bored. In order for the learning process to take place well, teachers need to prepare learning scenarios carefully and clearly so that students don't get bored and bored and get optimal learning outcomes, one of which is by using a learning model. The method used in writing this article is a qualitative literature study method. The subjects in this writing refer to 10 relevant journals. The results of the analysis noted that the Course Review Horay (CRH) learning model has an influence on student learning outcomes at the elementary school level. The average obtained for learning outcomes reached 33.4% with the lowest category 11%, the highest 65% and the average total completeness of learning outcomes after implementing the Course Review Horay (CRH) learning model was 62.65%. Based on this research, the Course Review Horay (CRH) learning model can be used as a new variation in the teaching and learning process, namely active and effective learning in elementary school students.